Social costs of obesity in the Czech Republic - Landovská, Petra; Karbanová, Martina (The European journal of health economics, 2023)
Increasing prevalence of obesity (BMI > 30) is a pressing public health issue in the Czech Republic as well as world-wide, affecting up to 2.1 billion people. Increasing trend in the prevalence of obesity in adults and children generates large social costs. The main aim of this study is to estimate both direct and indirect costs of obesity in the Czech Republic. Social costs of obesity are estimated using the cost-of-illness approach. Direct costs (healthcare utilization costs and costs of pharmacotherapy of 20 comorbidities) are estimated using the top-down approach, while indirect costs (absenteeism, presenteeism and premature mortality) are estimated using the human capital approach. In aggregate, the annual costs attributable to obesity in the Czech Republic in 2018 were 40.8 bn CZK (1.6 bn EUR, 0.8% GDP). Direct costs were 14.5 bn CZK (0.6 bn EUR) and accounted for 3.4% of Czech healthcare expenditures. The highest healthcare utilization costs were attributable to type II diabetes (20.6%), ischemic heart disease (18.8%) and osteoarthritis (16.7%). The largest indirect costs were attributable to premature mortality (10 bn CZK/0.39 bn EUR), absenteeism (9.2 bn CZK/0.36 bn EUR) and presenteeism (7.1 bn CZK/0.27 bn EUR). This article demonstrates that obesity is a serious problem with considerable costs. Several preventive interventions should be applied in order to decrease the prevalence of obesity and achieve cost savings.
Keywords: Obesity; Česká republika; Diabetes Mellitus, Type 2; osobní újma zaviněná nemocí; Cost-of-illness study; Adult; diabetes mellitus 2. typu; Czech Republic; Health Care Costs; dítě; náklady a analýza nákladů; Child; Humans; Delivery of Health Care; Cost of Illness; náklady na zdravotní péči; obezita; Social costs; poskytování zdravotní péče; dospělí; Costs and Cost Analysis; lidé